Scale economies can offset the benefits of competition: Evidence from a school consolidation reform in a universal voucher system - Monique de Haan; Edwin Leuven; Hessel Oosterbeek (Institute for the Study of Labor (IZA), 2011)
A large school consolidation reform in the Netherlands changed minimum school size rules underlying public funding. The supply of schools decreased by 15 percent, but this varied considerably across municipalities. We find that reducing the number of schools by 10 percent increases pupils' achievement by 3 percent of a standard deviation. A reduction in the supply of schools implies, for a given number of pupils, an increase in average school size. We present evidence that in our context scale economies dominated the effects of choice and competition. This points to an often ignored trade-off between scale and competition.
urn:nbn:de:101:1-201104114023
Keywords: I21; I22; H75; D40; 330; school choice; competition; school consolidation; achievement; economies of scale; Bildungsreform; Schulauswahl; Wettbewerb; Skalenertrag; Bildungsniveau; Niederlande